THE ADJECTIVES BODY IN THE LIGHT OF GENDER RELATIONS (Fiep Bulletin - online, 2011)
In society, a key concept for understanding the body is the body image. Body image is the "framework formed by the images or mental representations of the body that are presented to the individual in the context of his life" (Tavares, 2003, p.131). Environment and culture are also aspects that directly relate to the perception of our body. We notice that a periodic maintenance of our corporal perception exists, in view of that, the relation of the individual with the environment frequently is modified. This study investigates the perception of body image among boys and girls, through the interpretation of reports of children about their self-image. This research was conducted through a qualitative and quantitative study, which utilized a procedure for gathering data through reports made by students of a public school in Rio de Janeiro. We analyzed the reports of children of both sexes, in the Center for Integral Child Care (CAIC). Such children are studying in the fourth and fifth years of the first segment of basic education. The instrument used consists of two questions: 'what is the meaning of their body?' And 'how is your body?'. Based on the analysis of the reports from the children, the adjectives used to describe their bodies created such categories as aesthetic body, healthy, aesthetic and healthy, standard, full. It is observed that the more frequent category was the interpretation of body-based aesthetic with both the boys and the girls, with the surprising result of both positive and negative adjectives, with a higher incidence of negative adjectives in the girl's responses.
Keywords: body; culture; gender